Implementasi Sistem Penjaminan Mutu Eksternal di Sekolah Dasar Islam Terpadu Sabilul Huda - Hasan, Ali - (JIEM (Journal of Islamic Education Management), 2021)
This study aimed to reveal in depth about the application of external quality assurance Sabilul Huda Integrated Islamic Primary School (SHIIPS). This study used a descriptive qualitative approach. The technique of collecting data was triangulation. Data analysis was inductive in nature, external quality assurance in detail and accurately through the results of data derived from written data and documentation and oral interviews from related people. The results showed that the application of external quality assurance at SHIIPS can be categorized quite well, namely on graduate competency standards, curriculum content standards, process standards, educators and teaching staff standards, facilities and infrastructure standards, teaching unit management standards, education financing standards and grading standard